Perinatal outcome of monochorionic and dichorionic twins after spontaneous and assisted conception: a retrospective cohort study - Hack, Karien E.A. (Acta Obstet Gynecol Scand, 2018)
INTRODUCTION: The aim of this study was to compare pregnancy outcomes in twin pregnancies after assisted conception and spontaneous conception, according to chorionicity. MATERIAL AND METHODS: Retrospective cohort study of 1305 twin pregnancies between 1995 and 2015. All spontaneous (n = 731) and assisted conception conceived (n = 574) twin pregnancies with antenatal care and delivery in University Medical Center Utrecht, the Netherlands, a tertiary obstetric care center were studied according to chorionicity. RESULTS: Maternal age and incidence of nulliparity were higher among the assisted conception twins. Hypertensive disorders also appeared to be more frequent in assisted conception pregnancies, which could largely be explained by the higher proportion of elderly nulliparous women in this group. Spontaneously conceived twins were born earlier than twins after assisted conception, with subsequent lower birthweights and more admissions to a neonatal intensive care unit with increased neonatal morbidity. Monochorionic twins had worse pregnancy outcomes compared with dichorionic twins, irrespective of mode of conception; monochorionic twins conceived by assisted reproduction had more neonatal morbidity (mainly respiratory distress syndrome and necrotizing enterocolitis) and late neonatal deaths compared with spontaneously conceived monochorionic twins. CONCLUSIONS: Spontaneously conceived twins have worse pregnancy outcome compared with twins after assisted conception, probably due to a lower incidence of monochorionicity in the assisted conception group. The already increased perinatal risks in monochorionic twins are even higher in monochorionic twins conceived after infertility treatments compared with spontaneously conceived monochorionic twins, which warrants extra attention to these high‐risk pregnancies.